Pay or leave? The role of social media fatigue and willingness to pay to avoid fake news in social networks use - Dinu, Vasile; Pelau, Corina; Lile, Ramona; Boghicevici, Claudia (Journal of Business Economics and Management, 2024)
Social media networks are a technological phenomenon that has changed the entire social environment, as many real-world activities have shifted to posts or comments on social media. However, with this development several negative aspects have been revealed, such as information overload, privacy concerns and fake news. The aim of our research is to determine the impact fake news has on social media fatigue and discontinuous behavior and whether the willingness to pay to avoid fake news impacts this relationship. The results of two mediation models show that fake news positively affects social media fatigue, but there is no direct effect on the discontinuous use of social media. However, social media fatigue partly mediates the relationship between the awareness of fake news existence and discontinuous behavior. Furthermore, social media fatigue increases the willingness to pay for quality content, but contrary to our expectations, it does not reduce discontinuous behavior. This shows that the fake news phenomenon is far more complex, with other factors affecting it. Furthermore, imposing a price to avoid fake news is not a solution as users do not necessarily see value in this, but prefer to avoid social media so as not to have to deal with social media fatigue.